Multi-Omics Analysis of the Microbiome and Metabolome Reveals the Relationship Between the Gut Microbiota and Wooden Breast Myopathy in Broilers - Kang, Kelang; Zhou, Nanxuan; Peng, Weishi; Peng, Fang; Ma, Mengmeng; Li, Liwei; Fu, Fuyi; Xiang, Shuhan; Zhang, Haihan; He, Xi; Song, Zehe (Frontiers in Veterinary Science, 2022)
Wooden breast (WB) is a widely prevalent myopathy in broiler chickens. However, the role of the gut microbiota in this myopathy remains largely unknown, in particular the regulatory effect of gut microbiota in the modulation of muscle metabolism. Three hundred one-day-old Arbor Acres broilers were raised to 49 d and euthanized, and the breast fillets were classified as normal (NORM), mild (MILD), or severe wooden breast (SEV). Birds with WB comprised 27.02% of the individuals. Severe WB fillets had a greater L* value, a* value, and dripping loss, but a lower pH (P < 0.05). WB fillets had abundant myofiber fragmentation, with a lower average myofiber caliber and more fibers with a diameter of less than 20 μm (P < 0.05). The diversity of the intestinal microflora was decreased in birds with severe WB, with decreases in the Chao 1 and observed species indices. At the phylum level, birds with severe WB had a lower Firmicutes/Bacteroidetes ratio (P = 0.098) and a decreased abundance of Verrucomicrobia (P < 0.05). At the species level, gut bacteria were positively correlated with 131 digesta metabolites in pathways of glutamine and glutamate metabolism and arginine biosynthesis but were negatively correlated with 30 metabolites in the pathway of tyrosine metabolism. In plasma, WB induced five differentially expressed metabolites (DEMs), including anserine and choline, that were related to the severity of the WB lesion. The microbial-derived metabolites, including Guanidoacetic acid, Antiarol, and (2E)-Decenoyl-ACP, that entered into plasma were related to meat quality traits and myofiber traits. In summary, WB fillets differed in gut microbiota, digesta, and plasma metabolites. Gut microbiota respond to the wooden breast myopathy by driving dynamic changes in digesta metabolites that eventually enter the plasma.